ANÁLISE DO DIREITO À SAÚDE DO IDOSO (REMUNOM, 2023)
This article aims to study the guarantee of the right to health for the elderly. Seeking to discover whether the full application of what is set in the Statute of the Elderly and in the Federal Constitution with regard to the health of sixty-year-olds occurs, considering that the right to health of the elderly must be full, in order to guarantee the greatest right to society as a whole, which is the right to a full life.